Komposisi Dan Struktur Komunitas Ikan Pada Ekosistem Mangrove Di Perairan Teluk Benoa, Bali - I Putu Anggra Weda; I Wayan Restu; Ni Made Ernawati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The mangrove ecosystem of Benoa Bay is an estuarine area that plays a significant role in providing food sources for various types of biota, both aquatic and terrestrial. In addition, mangrove ecosystems are also greatly influenced by human activities such as development in mangrove areas and environmental pollution, which indirectly affect the presence of biota in those mangrove ecosystems. The purpose of this research is to understand the fish community structure and water conditions in the mangrove ecosystem of Benoa Bay. This research was conducted in October – November 2023 at 4 stations with 2 repetitions at each station. Fish sampling using gill nets with a mesh size of 2 inches.  The fish catch results in the Teluk Benoa mangrove ecosystem consist of 8 families and 10 species. Station II has the highest fish abundance among the other stations, with 8 species, while the lowest fish abundance is found at Station III, with 5 species. The fish species most commonly found in Benoa Bay is Leiognathus equulus or Cotek Fish, with a total of 188 individuals. Meanwhile, the fish species with the least number are Tripoddichthys blochii and Lobotes surinamensis, with only 1 individual each.